Hubungan Status Gizi Dan Status Ekonomi Dengan Kejadian Anemia Pada Remaja Putri - Sondakh, Levana; Katili, Dwi Nur Octaviani; Melani, Nour Arriza Dwi; Yunus, Yuliandary; Latief, Miftahuljannah (Madu : Jurnal Kesehatan, 2025)
Adolescent girls have a high risk of experiencing anemia, as this is a period when there is an increase in iron needs due to growth and menstruation, and the impact of anemia on adolescent girls is a decrease in endurance, fitness and agility of thinking, and impacts during pregnancy. The aim of this research is to determine the relationship between nutritional and economic status and anemia in adolescent girls. The research design used a quantitative with an analytical survey and a cross-sectional approach. The total population was 32 people, with a sample size of 32 people or total sampling. The results showed that the highest economic status of the student’s parents was the upper-class economic status, with 19 people, and the p-value = 0.022 < 0.05. The highest nutritional status of the students was normal, with 23 people, and the p-value = 0.000 < 0.05. There was a relationship between economic status and nutritional status with anemia in adolescent girls in the work area of the Dumbo Raya Public Health Center, Gorontalo City.